2001
DOI: 10.1089/105072501753271789
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Ovarian Metastasis from Papillary Thyroid Carcinoma: A Case Report

Abstract: Ovarian metastasis from a primary thyroid carcinoma is rare. In this report we describe a woman who manifested the unusual occurrence of metastases of papillary thyroid carcinoma to the ovary. Both clinically and pathologically, such a presentation can be difficult to distinguish from benign cystic neoplasms of the ovary or cystic struma ovarii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(26 citation statements)
references
References 11 publications
0
25
0
1
Order By: Relevance
“…The rarity of ovarian metastasis from DTC is supported by a review of the literature, where only three cases have been reported (Young et al 1994, Logani et al 2001, Brogioni et al 2007. It seems that ovarian metastasis tends to occur unilaterally rather than bilaterally (Fig.…”
Section: Ovarian Metastasismentioning
confidence: 94%
“…The rarity of ovarian metastasis from DTC is supported by a review of the literature, where only three cases have been reported (Young et al 1994, Logani et al 2001, Brogioni et al 2007. It seems that ovarian metastasis tends to occur unilaterally rather than bilaterally (Fig.…”
Section: Ovarian Metastasismentioning
confidence: 94%
“…Differential diagnosis for mediastinal thyroid includes germ cell tumors, neurogenic tumors, lymphomas, and thymic and mesenchymal tumors (36). Struma ovarii must be distinguished from primary ovarian tumors, such as granulosa cell tumors, Brenner tumors, papillary serous cystadenomas or cystadenocarcinomas, struma carcinoid, or rare cases of differentiated thyroid carcinoma metastatic to the ovary (78,79). The other intra-abdominal ectopies are usually incidental findings and diagnosis is based on histological examination.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…There are two reports of nonfunctioning struma ovaries diagnosed incidentally after iodine therapy for which oophorectomy was performed immediately [2,3]. A very rare case was reported of cystic ovarian metastasis from papillary thyroid cancer that was diagnosed on a post-therapy whole-body scan with increasing thyroglobulin, and also confirmed on pelvic surgery [4]. In contrast to the above cases with immediate surgery after a presumptive diagnosis, one patient was diagnosed with possible benign struma ovarii on postablation scan and ovarian surgery was postponed for 6 months [5].…”
Section: Discussionmentioning
confidence: 99%